The Influence of Modernity on Matn Criticism: A Comparative Study of Traditionist and Reformist Approaches in Ibn Hajar’s Fath al-Bari and Rashid Rida’s Majallat al-Manar on Hadiths of Natural Phenomena - Al-Imam, Ahmad Abdur Rahman (Journal of Islamic Thought and Civilization, 2026)
This study examines the influence of modernity on matn (hadith text) criticism through a comparative analysis of traditionist and reformist approaches to selected hadiths concerning natural phenomena. It focuses on the reformist engagement of Rashid Rida (d. 1935) in Majallat al-Manar (The Lighthouse Journal), and contrasts it with the traditionist methodology exemplified by Ibn Hajar al-ʿAsqalani’s (d. 1449) Fath al-Bari (Victory of the Creator). The article analyzes how Rida revisits established principles of matn criticism when engaging with hadiths that intersect with modern scientific sensibilities, while Ibn Hajar’s commentary illustrates the classical traditionist framework for evaluating matn coherence. The study selects two widely discussed reports—the hadith of the fly and its immersion in drink, and the hadith of the sun prostrating beneath God’s Throne—as case studies. These reports are chosen on the basis that their isnad (chain of transmission) is generally deemed sound within the traditionist framework, thereby allowing the analysis to concentrate primarily on matn evaluation rather than transmission criticism. Through close textual analysis, the article demonstrates that reformist matn criticism tends to prioritize rational coherence and empirical plausibility, whereas traditionist scholarship emphasizes reconciliation (jamʿ), contextualization, and interpretive restraint, often favoring face-value readings and limited taʾwīl. The article argues that modernity introduced an epistemological reconfiguration within hadith criticism, prompting divergent evaluative criteria rather than a rejection of the tradition itself. By foregrounding matn-centered analysis, this study contributes to contemporary scholarship by clarifying how shifting epistemic assumptions shape distinct paradigms of hadith interpretation.